Analisis Penerapan PSAK No. 24 Tentang Imbalan Kerja: Studi Kasus pada PT. XYZ - Zumrotil Auliya; Rini Febrianti; Putri Nailah Azahra; Dhio Gon zales; Siti Rodiah (Jurnal Ilmiah Manajemen Ekonomi Dan Akuntansi (JIMEA), 2025)
This study aims to analyze the implementation of Financial Accounting Standards Statement (PSAK) No. 24 concerning Employee Benefits at PT. XYZ, a construction service company currently in the development stage. The study uses a qualitative descriptive approach with data collected through interviews with the company’s management and permanent employees. The results show that PT. XYZ has implemented short-term employee benefits such as salaries, fixed allowances, bonuses, overtime pay, paid leave, and social security in accordance with PSAK 24 regulations. However, the company has not yet implemented post-employment benefits, other long-term employee benefits, or termination benefits. This is due to the company's early stage and focus on operational and financial stabilization. The study recommends developing long-term employee benefits policies and more comprehensive employment documentation to ensure PT. XYZ's financial reporting complies with applicable accounting standards.